Contact dynamics and control of a space robot capturing a tumbling object. (October 2018) - Wu, Shuang; Mou, Fangli; Liu, Qian; Cheng, Jing
Abstract: Capture of a free-floating space object in orbit is a challenging task especially when the object is tumbling. In this paper, the contact dynamics modeling and control problem for capturing a fast tumbling target object by a space robot are investigated. A generic frictional contact model is developed to represent the contact forces between the robot's end-effector and the target object. The frictional contact formulation is based on the compliance contact force and bristle friction model which can simulate intermittent frictional contact situations involving multiple-point contacts between contact interfaces with complex geometries. A resolved motion admittance control method is designed to realize a good tracking for a tumbling target object while increasing the compliance of the space robot. A simulation example of a 7-joint manipulator capturing a tumbling object in three dimensions is presented. The simulation results revealed that various contact scenarios during the capture process can be well simulated with the developed contact model and a good performance of the designed control method for capturing a fast tumbling target object. Highlights: A frictional contact force model is developed to describe general 3-D contact scenarios. The proposed contact model can simulate intermittent frictional contact with complex geometry. A RMAC method is introduced for controlling a robotic arm to capture a tumbling object. Simulation showed successful grasping of an object tumbling at 8 deg/s in magnitude.